Enhancement of the Efficiency of the CZTS/Cds/Zno/ITO Solar Cell By Back Reflection and Buffer Layers Using SCAPS -1D - Ganem, Hardan T.; Saleh, Ayed N. (Iraqi Journal of Science, 2021)
CZTS / CdS / ZnO / ITO solar cell was studied using Solar Cell Capacitance Simulato-1D (SCAPS-1D) program. We performed an improvement on the theoretical cell by increasing the doping and thickness of some layers. As a result, the efficiency was shifted from 2.18% to 6.17% and several back reflection layers (BSL) were introduced on the enhanced cell until. We obtained a highest conversion efficiency of 13.99%. The best reflection layer (CZTSSe) was combined with the best buffer layer (CdSe), with thickness of 0.9µm, on the enhanced cell. Thereby, we obtained a cell with a conversion efficiency of 16.53%. A second improvement was made to the best obtained cell, where the CZTSSe with thickness of 0.05µm and the CdSe with thickness of 0.9µm were combined. Consequently, the efficiency was increased from 16.53% to 21.76%. By comparing the experimental results with those obtained with the program, it was found that the program simulates reality, i.e. the experimental and theoretical results matched.